Perspektif Hukum Islam Dan Hukum Positif Di Indonesia Tentang Perkawinan Usia Dini Serta Dampaknya Bagi Keluarga - Suhendra, Darmiko (Fakultas Syariah dan Ekonomi Islam, IAIN Syaikh Abdurrahman Siddik, Bangka Belitung, 2024)
Man in the process of its development to continue its kind requires a spouse who can give offspring in accordance with what he wants. The establishment of a happy and lasting family must be based on religious and legal norms. Marriage for human beings is important, because with a marriage a person will get the balance of life both biologically, psychologically and socially.Marriage is commonly done by adults (baligh) regardless of profession, religion, ethnicity, poor or rich. Extremely overly wedded marriages result in divorce cases, due to a lack of awareness to be responsible in married life for husband and wife. Marriage is not as simple as imagined. Need maturity both in psychology and physical. Efforts to realize the family sakinah and happy, one of which is to prevent the occurrence of marriage a young age. And the minimum effort that is usually taken is the implementation of the maturation program of marriage age and the planning of family life is one of the requirements for the realization of sakinah, mawaddah and rahmah families.